Paths to literacy and numeracy problems: evidence from two British birth cohorts. Issue 3 (21st August 2008) - Richards, M; Power, C; Sacker, A
Abstract : Background: To test a life course model linking circumstances of origin to self-reported literacy and numeracy problems in midlife, and to investigate the effects in this model of changing social circumstances in two post-war cohorts. Methods: Based on data from men and women in the British 1946 and 1958 birth cohorts, we used the relative index of inequality and logistical regression to test associations between father's occupation, childhood cognition, educational attainment, own occupation in the third decade, and a binary variable representing self-reported literacy and numeracy problems in the fourth decade. Results: There was a lower frequency of literacy and numeracy problems in the 1958 cohort than in the 1946 cohort. In both cohorts there were associations between father's occupation and childhood cognition, educational attainment and own occupation, a pattern that was mirrored by the associations between childhood cognition, educational attainment and own occupation to adult literacy and numeracy problems. Positive associations between childhood cognition and educational attainment, and between educational attainment and own occupation, were stronger in the 1946 cohort than in the 1958 cohort. However, inverse associations between educational attainment and literacy and numeracy problems were stronger in the 1958 cohort, possibly reflecting the expansion of secondary education in the intervening years. Conclusions: Literacy and numeracy problems have a robust structure of life course associations, although the changing pattern of these associations may reflect important social structural changes from the early post-war years to the early 1960s in the UK.